String Matching Pada Pencarian Di Web Jurnal Menggunakan Algoritma Knuth Morris Pratt (KMP) (PETIR, 2023)
This research aims to: (1) enhance the responsiveness of a journal website for easier access from mobile devices and improve the quality of its appearance and user experience during web browsing, (2 enabling easy access to information and visibility, and (3) improve the data processing of the journal by effectively utilizing the Knuth Morris Pratt (KMP) algorithm. The subjects of this research are the user interface and user experience of the web journal application for students, learners, and the general public, while the object of this research is the web journal application itself. The data sources used consist of secondary data obtained from books, documents, and archives containing relevant information. This research employs data collection techniques by gathering information from pre-existing data sources such as books, journals, reports, the internet, and other documents. The estimated time required to conduct this research is two months (November-December 2022). This research develops a responsive web journal using the Laravel Framework and the Knuth Morris Pratt (KMP) algorithm for journal data search. The implementation of the KMP algorithm resulted in a search time of approximately 0.505 seconds with 15 keywords.